Dinamika Penyesuaian Diri Caregiver Orang dengan Gangguan Jiwa (ODGJ) di Yayasan Karya Asih Lawang - Jihan Safitri; Aryudho Widyatno (Fakultas Psikologi Universitas Negeri Malang, 2021)
Formal caregivers for patients with mental ilnesses have psychological risks during handling patients which include stress, fear, and trauma. Efforts to overcome these conditions require an adjustment on formal caregivers to provide appropriate and effective services for people with mental illnesses. This research aims to determine the dynamic of the caregiver adjustment process in Yayasan Karya Asih. This research design use a qualitative approach with case study model. Data collection method using semi-structured interview and qualitative questionnaire given to 9 permanent employees who work as caregiver in Yayasan Karya Asih. The analytical technique used is thematic analysis technique. Based on the result of this research, it can be conclude that The caregivers for people with mental illnesses in Yayasan Karya Asih have adjusted to the chosen job, it can be seen from choice of work that in line with the field of work, sense stability and adaptability to various working conditions (patients, work colleagues, task, and environment). In the process there are several things that help and dynamics of the adaptation process of the caregivers of people with mental illnesses in Yayasan Karya Asih such as: 1) similarity of individual background; 2) co-worker support; 3) the role of providing education; 4) coping strategy; and 5) experience. Efforts to adjust with patients with mental illnesses can be done by understanding the patients’ character in order to determine the right strategy to handling cases for treated patients with mental illnesses.